2020
DOI: 10.1016/j.acra.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Radiologist Workflow Improves Report Value and Saves Time: A Potential Model for Implementation of Artificial Intelligence

Abstract: Small Bowel Obstruction Rationale and Objectives: Our primary aim was to improve radiology reports by increasing concordance of target lesion measurements with oncology records using radiology preprocessors (RP). Faster notification of incidental actionable findings to referring clinicians and clinical radiologist exam interpretation time savings with RPs quantifying tumor burden were also assessed. Materials and Methods: In this prospective quality improvement initiative, RPs annotated lesions before radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Furthermore, variations in NM physicians' recognition of and the lack of defined standardized features on the images also contribute to variability in thyroid disease diagnosis. Machine learning will be an effective solution to the shortage of medical resources, 21 especially with regard to automatic diagnosis of thyroid scintigraphy studies. [22][23][24][25] The principal purpose of this paper is to describe the design of classifier models using different DL algorithms for the diagnosis of Graves' disease and subacute thyroiditis by thyroid scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, variations in NM physicians' recognition of and the lack of defined standardized features on the images also contribute to variability in thyroid disease diagnosis. Machine learning will be an effective solution to the shortage of medical resources, 21 especially with regard to automatic diagnosis of thyroid scintigraphy studies. [22][23][24][25] The principal purpose of this paper is to describe the design of classifier models using different DL algorithms for the diagnosis of Graves' disease and subacute thyroiditis by thyroid scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Such annotations have been used effectively for labeling of open-source data sets (60). Measurements can be performed in advance of radiologists by radiology preprocessors that improve annotation quality while saving radiologists time (61). Preliminary work on prospective labeling is showing that twodiameter measurements and ovals are better than one-diameter measurements and much better than arrows (62).…”
Section: Ground Truth or Label Qualitymentioning
confidence: 99%
“…This can help expedite workflows, improve accuracy, and ultimately reduce overall costs. 3 Recent work has focused on chest radiography, the most common imaging examination conducted in emergency departments (EDs) and urgent care settings. Several studies have reported machine learning models achieving radiologist-level performance for different chest radiograph findings.…”
Section: Introductionmentioning
confidence: 99%